Economic burden of infectious diseases and its equity implications in Indian households: Estimates from a nationally representative household survey (2017–18) - Habib Hasan Farooqui; Anup Karan; Giridhar R. Babu; Suhaib Hussain; Onno C.P. van Schayck (Social Sciences and Humanities Open, 2024)
Infectious diseases remain one of the major causes of health and economic burden for Indian households. Furthermore, the magnitude of economic losses on account of infectious disease episodes varies widely across rich and poor households. The primary objective of this research is to estimate the equity impact of infectious disease episodes on out-of-pocket expenditure (OOPE) and wage losses among Indian households. We analysed the Social Consumption: Health (SCH) data from the 75th round (2017–18) of India's National Sample Survey (NSSO). The sample included approximately 113,823 households and 555,352 individuals through a multistage stratified sampling process. We report i) the prevalence of infectious disease and healthcare utilisation rate by levels of care; ii) medical and non-medical OOPE per episode; iii) OOPE and wage loss as a share of households' monthly non-medical consumption expenditure (non-medical MPCE) across wealth quintiles. We adopted a microeconomic cost of illness approach to estimate the OOPE on infectious disease episodes for outpatient care and hospitalization. We also estimated potential wage losses due to a reduction in effective labour supply at the household level because of infectious disease using a production function approach. The overall prevalence of infectious diseases and hospitalization rate were 31 and 9 per thousand persons, respectively. Per capita medical OOPE was more in higher wealth quintiles for outpatient care and hospitalization. However, OOPE as a share of non-medical MPCE was higher in the poorest 20% households (outpatient: 14%; hospitalization: 153%) in comparison to the richest 20% households (outpatient: 5.5%; hospitalization: 96%). Similarly, the wage losses as a share of non-medical MPCE were higher among the poorest 20% households (outpatient: 21%; hospitalization:38%) in comparison to the richest 20% households (outpatient: 15%; hospitalization:11%). Furthermore, the proportion of households reporting the sale of assets and borrowing to finance hospitalization was higher in the poorest (24%) compared to the richest (12.5%). To our knowledge, this is the first paper which contributes to developing an understanding of the equity impact of infectious disease on households in India. We recommend improved targeting and coverage of publicly funded health insurance schemes among socially disadvantaged populations.